2013
DOI: 10.1002/qua.24579
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic modeling toward high-efficiency carbon capture: A brief survey with a few illustrative examples

Abstract: With the negative environmental implications of the anthropogenic emission of greenhouse gases like CO 2 having been scientifically established, emphasis is being placed on a concerted global effort to prevent such gases from reaching the atmosphere. Especially important are capture efforts at large point emission sources like fossil fuel power generation, natural gas processing, and various industrial plants. Given the importance and scale of such activities, it is a significant priority to optimize the captu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 123 publications
(190 reference statements)
0
17
0
Order By: Relevance
“…The H 2 /SF 6 and H 2 /CH 4 ideal permselectivities are higher than 500 and 15, respectively, well above the respective values for the Knudsen selectivity of 8.5 and 2.8. SF 6 can only diffuse through defects in the zeolite lm. Diffusion of adsorbing gases through 8MR zeolites at moderate temperatures is governed by surface diffusion.…”
Section: Single Gas Permeationmentioning
confidence: 99%
See 1 more Smart Citation
“…The H 2 /SF 6 and H 2 /CH 4 ideal permselectivities are higher than 500 and 15, respectively, well above the respective values for the Knudsen selectivity of 8.5 and 2.8. SF 6 can only diffuse through defects in the zeolite lm. Diffusion of adsorbing gases through 8MR zeolites at moderate temperatures is governed by surface diffusion.…”
Section: Single Gas Permeationmentioning
confidence: 99%
“…4 Capturing CO 2 is technologically very challenging and it is estimated to account for 50-90% of the total cost in the CCS/CCU chain. 6,7 Drawbacks of this industrial process are the cyclic operation and the high energy penalty. 6,7 Drawbacks of this industrial process are the cyclic operation and the high energy penalty.…”
Section: Introductionmentioning
confidence: 99%
“…16 Should CO 2 exhibit higher affinity to the rock formations than hydrocarbons, it could help increase production. Understanding the relation between competitive adsorption and transport of CO 2 and hydrocarbons in rock formations is considered crucial to optimize both CO 2 storage capacity 17 and natural gas production.…”
Section: Introductionmentioning
confidence: 99%
“…236 The importance of considering the dipole and quadrupole moments of solutes was also highlighted when looking at the solubility of gases in ionic liquids; this area has gained much attention in recent years, mainly focused around capture and storage of greenhouse gases. [240][241][242][243] A classical molecular dynamics study investigated the solubility of a number of different gases in the ionic liquid [Emim][N(SO 2 CF 3 ) 2 ]; they found that both hydrogen sulphide (which has a signicant dipole moment) and carbon dioxide (no dipole moment but with a large quadrupole moment), were highly soluble. In contrast, molecular hydrogen and nitrogen, with no dipole or quadrupole moments, were much less soluble.…”
Section: Case Studies: the Utility Of Combining Computational And Expmentioning
confidence: 99%